ANALISIS KESALAHAN BERBAHASA INDONESIA TATARAN FONOLOGI PENYIAR RADIO REPUBLIK INDONESIA (RRI) TERNATE - Farlina Rustam; Sulami Sibua; Anwar Nada (FKIP Universitas Khairun, 2021)
This study aims to describe the Indonesian language errors in the speech of the radio announcer of the Republic of Indonesia (RRI) Ternate. There are two formulations of the problem in this study, namely (1). What is the form of error in the omission of phonemes in the speech of the broadcaster of Radio Republik Indonesia (RRI) Ternate? (2). What are the errors in adding phonemes in the speech process of the broadcaster of Radio Republik Indonesia (RRI) Ternate. The objectives of this research are: (1). Explain the forms of omission of phonemes contained in the speech of the broadcaster of Radio Republik IIndonesia (RRI) Ternate. (2) Explaining errors in adding phonemes in the speech process of the broadcaster of Radio Republik Indonesia (RRI) Ternate. The method used in this research is a qualitative method with a descriptive approach. The collection techniques used in this research are listening and recording techniques.Based on the data that has been obtained, the researcher analyzes the data to look for errors that occur during the broadcasting process, such as pronunciation errors due to omission of phonemes and pronunciation errors due to addition of phonemes. The results of the analysis of errors in Indonesian at the phonological level of the radio broadcaster of the Republic of Indonesia (RRI) Ternate, there are forms of pronunciation errors, namely pronunciation errors due to omission of phonemes and pronunciation errors due to addition of phonemes. The omission of a phoneme is the loss of one phoneme in a whole word, while the addition of a phoneme occurs because the speaker adds a phoneme to a word.